Cytokine storm intervention in the early stages of COVID-19 pneumonia - Xinjuan Sun; Tianyuan Wang; Dayong Cai; Zhiwei Hu; Jinan Chen; Hui Liao; Liming Zhi; Hongxia Wei; Zhihong Zhang; Yuying Qiu; Jing Wang; Aiping Wang (2020)
Clinical intervention in patients with corona virus disease 2019 (COVID-19) has demonstrated a strong upregulation of cytokine production in patients who are critically ill with SARS-CoV2-induced pneumonia. In a retrospective study of 41 patients with COVID-19, most patients with SARS-CoV-2 infection developed mild symptoms, whereas some patients later developed aggravated disease symptoms, and eventually passed away because of multiple organ dysfunction syndrome (MODS), as a consequence of a severe cytokine storm. Guidelines for the diagnosis and treatment of SARS-CoV-2 infected pneumonia were first published January 30th, 2020; these guidelines recommended for the first time that cytokine monitoring should be applied in severely ill patients to reduce pneumonia related mortality. The cytokine storm observed in COVID-19 illness is also an important component of mortality in other viral diseases, including SARS, MERS and influenza. In view of the severe morbidity and mortality of COVID-19 pneumonia, we review the current understanding of treatment of human coronavirus infections from the perspective of a dysregulated cytokine and immune response.